Professional trajectories of women teachers in the engineering area of a private university in Peru - Espinoza Adarmes, Nataly (2020)
The aim of this study was to analyze the perceptions of women engineering teachers about their professional trajectories. Regarding the methodology, the qualitative approach and the phenomenological method were chosen. In addition, six female teachers of the engineering area were interviewed. The main findings indicated that the motivations to redirect their professional path towards teaching were the acknowledgments, the promotion of research and schedules’ flexibility, despite not considering it as the first option of professional development. Also, teaching provided them with opportunities to pursue graduate studies without restrictions, to care for their families and to postpone motherhood. However, working at a university meant facing organizational obstacles, such as differences in treatment according to gender and age, as well as practices of exclusion and favoritism.